2018
DOI: 10.1002/jcsm.12316
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory placental‐expanded, mesenchymal stromal cells improve muscle function following hip arthroplasty

Abstract: BackgroundNo regenerative approach has thus far been shown to be effective in skeletal muscle injuries, despite their high frequency and associated functional deficits. We sought to address surgical trauma‐related muscle injuries using local intraoperative application of allogeneic placenta‐derived, mesenchymal‐like adherent cells (PLX‐PAD), using hip arthroplasty as a standardized injury model, because of the high regenerative and immunomodulatory potency of this cell type.MethodsOur pilot phase I/IIa study w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 40 publications
(37 reference statements)
2
60
0
2
Order By: Relevance
“…A statistically significant reduction of stress leaks in all dose groups was observed compared with baseline . In the first clinical study of its kind, skeletal muscle injury associated with hip arthroplasty surgeries was treated by local administration of allogeneic placenta‐derived MSCs in a small cohort of patients . Cells were delivered intraoperatively after thawing.…”
Section: Translating Pre‐clinical Promise Into Clinically Successfulmentioning
confidence: 99%
“…A statistically significant reduction of stress leaks in all dose groups was observed compared with baseline . In the first clinical study of its kind, skeletal muscle injury associated with hip arthroplasty surgeries was treated by local administration of allogeneic placenta‐derived MSCs in a small cohort of patients . Cells were delivered intraoperatively after thawing.…”
Section: Translating Pre‐clinical Promise Into Clinically Successfulmentioning
confidence: 99%
“…In a randomized phase I/IIa study (NCT01525667) conducted by Pluristem Therapeutics (Haifa, Israel), 20 patients undergoing hip arthroplasty received an injection of either 300 or 150 million placental‐expanded, mesenchymal stromal cells or placebo into the surgically affected gluteus medius muscles. In this study, both treatment arms demonstrated greater improvement in gluteus medius muscle strength at 6, 12, and 26 weeks after surgery . Pluristem is currently planning a study to assess the efficacy of similar treatment in individuals after hip fracture (NCT03451916).…”
Section: Nonpharmacological Regenerative Medicine Approachesmentioning
confidence: 80%
“…In this study, both treatment arms demonstrated greater improvement in gluteus medius muscle strength at 6, 12, and 26 weeks after surgery. 78 Pluristem is currently planning a study to assess the efficacy of similar treatment in individuals after hip fracture (NCT03451916).…”
Section: Nonpharmacological Regenerative Medicine Approaches Stem Cellsmentioning
confidence: 99%
“…(Local) reduction of conventional T‐cell levels and concurrent enrichment of regulatory T cells is a promising therapeutic strategy to further improve muscle repair. In this regard, Winkler et al . (Charité University Berlin, Berlin, Germany) presented data from the HIPGEN study, which is now in Phase III.…”
Section: Clinical Trials and New Treatment Targetsmentioning
confidence: 99%
“…(Local) reduction of conventional T-cell levels and concurrent enrichment of regulatory T cells is a promising therapeutic strategy to further improve muscle repair. In this regard, Winkler et al 48 (Charité University Berlin, Berlin, Germany) presented data from the HIPGEN study, which is now in Phase III. This randomized, double-blind, placebo-controlled study addresses surgical trauma-related muscle injuries using local intraoperative application of allogeneic placentaderived, mesenchymal-like adherent cells, using hip arthroplasty as a standardized injury model, because of the high regenerative and immunomodulatory potency of this cell type.…”
Section: Clinical Trials and New Treatment Targetsmentioning
confidence: 99%